Formal [5+2] cycloaddition of vinylethylene carbonates to oxazol-5-(4H)-ones for the synthesis of 3, 4-dihydrooxepin-2(7H)-ones. Issue 66 (31st July 2018) - Zhao, Hong-Wu; Du, Juan; Guo, Jia-Ming; Feng, Ning-Ning; Wang, Li-Ru; Ding, Wan-Qiu; Song, Xiu-Qing
Abstract : Formal [5+2] cycloaddition of vinylethylene carbonates to oxazol-5-(4 H )-ones. Abstract : Under the catalysis of Pd2 (dba)3 (2.5 mol%), PPh3 (10.0 mol%) and TMSCl (1.0 eq.), the formal [5+2] cycloaddition of vinylethylene carbonates to oxazol-5-(4 H )-ones proceeded readily in THF at 60 °C to r.t., thus furnishing 3, 4-dihydrooxepin-2(7 H )-ones in 67–99% chemical yields. The chemical structure of one compound was confirmed by X-ray diffraction analysis, and the others were suggested by inference.